2018
DOI: 10.1039/c8ob01617h
|View full text |Cite|
|
Sign up to set email alerts
|

Stepwise triple-click functionalization of synthetic peptides

Abstract: A sequence of click reactions and selective deprotection steps enables the stepwise synthesis of defined triple-functionalized peptides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Con A can be readily obtained from natural sources (jack‐bean) in large quantities and is also commercially available, making it an ideal candidate for our proof‐of‐concept study. Based on our previous work, [16] we constructed a one‐bead‐one‐compound (OBOC) glycopeptide library. This library was carefully designed to contain α‐ d ‐mannose‐ and α‐ d ‐glucose moieties at defined positions.…”
Section: Resultsmentioning
confidence: 99%
“…Con A can be readily obtained from natural sources (jack‐bean) in large quantities and is also commercially available, making it an ideal candidate for our proof‐of‐concept study. Based on our previous work, [16] we constructed a one‐bead‐one‐compound (OBOC) glycopeptide library. This library was carefully designed to contain α‐ d ‐mannose‐ and α‐ d ‐glucose moieties at defined positions.…”
Section: Resultsmentioning
confidence: 99%
“…There is a significant interest in developing bioorthogonal chemistry that allows targeting more than one position individually. [57][58][59][60] The finding that bulky tert-butyl groups increase the rate of the isonitriletetrazine reaction while effectively blocking the approach of alkene-based dienophiles naturally allows for developing orthogonal reactant pairs. Leeper et al had already shown previously that isonitriles are orthogonal to azide-alkyne reactions.…”
Section: Account Syn Lettmentioning
confidence: 99%
“…Noteworthy, the preparation of peptide-based bioimaging probes can take advantage of the rich chemical toolbox of peptide chemistry that enables their straightforward synthesis and functionalization, strongly expanding their potential applications and utility. Peptide functionalization is usually performed in solid phase during on-resin peptide synthesis, and it often requires complex orthogonal protection/deprotection schemes. Peptide functionalization in solid phase, although ensuring a high level of specificity, usually proceeds under harsh conditions, and it is not always well tolerated by the imaging moieties; furthermore, it is expensive due to the consumption of large excesses of precious reactants and it is not environmentally sustainable, being that the synthetic steps are completely performed in organic solvents. The development of cost-effective and greener chemical procedures enabling the site-specific functionalization of peptide sequences under mild conditions is strongly desired to further the effective wide spreading of peptide-probes in bioimaging.…”
Section: Introductionmentioning
confidence: 99%